2006
DOI: 10.1002/pd.1531
|View full text |Cite
|
Sign up to set email alerts
|

Fetal abnormalities leading to termination of singleton pregnancy: the 7‐year experience of a single medical center

Abstract: The impact of early chromosomal/genetic screening contributes to early TOPs, while midgestation anomaly and cardiac scanning significantly contribute to late TOPs. Fetal infection contributes equally to both categories of TOPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
27
5
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 14 publications
13
27
5
4
Order By: Relevance
“…The reason for this rise may be the growing use of echocardiogram as a complementary scan, as well as the increasing experience of fetal heart screening among the obstetricians in Turkey. In our series, the most common chromosomal anomaly was trisomy 21, which was consistent with the other studies (4,7,8).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The reason for this rise may be the growing use of echocardiogram as a complementary scan, as well as the increasing experience of fetal heart screening among the obstetricians in Turkey. In our series, the most common chromosomal anomaly was trisomy 21, which was consistent with the other studies (4,7,8).…”
Section: Discussionsupporting
confidence: 82%
“…Central nervous system anomalies accounted for more than half of the indications for both early and late terminations. This finding is consistent with the studies which showed that central nervous system malformations are the most common structural malformations leading to the TOP (4,7,8,12,13). Fetal autopsy has a particularly valuable role in the counseling of families after the TOP (14).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Erken terminasyonların aksine geç terminasyonların en sık nedeni, fetal yapısal anomaliler olup, bunlar içinde en sık görülen fetal yapısal anomaliler MSS anomalileridir (9,11,14,15,16) . Hidrosefali, korpus kallosum agenezisi ve lizensefali gibi genellikle ikinci ve erken üçüncü trimesterde belirgin hâle gelen MSS anomalilerinin geç terminasyonlardaki sıklığı daha fazladır (11) .…”
Section: Discussionunclassified
“…The malformations constitute the most frequent indication for termination of pregnancy. This group include different pathologies in which skeletal system is a small percentage variable between 6% and 16% [30][31][32]. Although most of the TA referred to our laboratory came from private centre with no medical or anatomic record, we have diagnosed 30% of TA (5 skeletal dysplasias and 1 triploidy) from 20 cases.…”
Section: Discussionmentioning
confidence: 99%